Upaya Penangulangan Kekerasan Seksual Terhadap Anak di Aceh Barat dalam Persepektif Hukum Islam - Sumardi Efendi; Dar Kasih (IAIN Langsa, 2022)
This article examines efforts to tackle sexual violence against children in West Aceh from the perspective of Islamic law. This writing aims to find out the problem of sexual violence against children and how the proposed solution is based on the view of Islamic law. The data collection method in this article is using library research. Secondary data was obtained by studying the rules and regulations and literature related to this article. Cases of sexual violence against children in 2021 West Aceh Regency based on data from the Integrated Service Center for the Empowerment of Women and Children (P2TP2A) West Aceh had 5 cases of sexual violence. The percentage of cases of sexual violence is relatively high, namely 27.7 percent of the total 18 cases of violence against children. The sanctions that can be imposed on perpetrators of sexual violence against children in Islam are jarimah hudud, jarimah qishas and diat, and jarimah ta'zir. Special sanctions for perpetrators of child sexual violence can be subject to criminal sanctions in the form of Takzir whose determination of punishment is the right of ulil amri. The countermeasures that can be carried out are by socializing the 4P program (Assistance, Protection, Imposition of Sanctions, and Recovery) to the community.